Perancangan Brand Guideline Klub Sepakbola PSIM Jogja Sebagai Upaya Meningkatkan Brand Image - Ditya Fajar Rizkizha (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2023)
The inconsistency of visual identity of PSIM Jogja Football Club (FC) promoting different perception to its supporters. During its course, the visual identity of PSIM Jogja FC appears to be inconsistent on various branding media. The purpose of this study is to design brand guideline for PSIM Jogja FC based on the visual identity guideline and standard of the organization. Using qualitative method with cultural approach, this study obtained data from direct observations and interviews to the management and supporters of PSIM Jogja FC. The development of the design is divided into three stages, i.e., idea, planning, and implementation based on design thinking framework. The results show the design as a mean to develop locality element as an identity to be used as a benchmark for the owned history and cultural values to strengthen the forming of an identity.